Optimalisasi Kesiapan Uji Kompetensi Simulasi Rapat: Program Pendampingan Siswa SMK Abdi Bangsa Kota Sukabumi - Derry Nugraha; Dini Hermalia; Clarita Nuraeni (CV. Era Digital Nusantara, 2025)
This community service program aims to enhance the competency of students at SMK Abdi Bangsa Sukabumi City in preparing for meeting simulation competency tests. The mentoring was conducted over three months involving 45 students using a descriptive qualitative approach. Data collection methods included participatory observation, in-depth interviews, and focus group discussions. Results showed significant improvements in meeting protocol mastery, communication skills, and digital technology adaptation, with 85% of participants demonstrating good understanding of formal meeting procedures. The program successfully increased participants' confidence, with 80% reporting improved ability to express opinions, and 90% showing proficiency in using online meeting platforms. Program sustainability is ensured through systematically developed mentoring systems and best practices documentation, providing a strong foundation for future implementation.